PROFIL TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPCK) MAHASISWA CALON GURU BIOLOGI FKIP UNIVERSITAS RIAU - Suryawati, Evi Suryawati Evi; Arief, Raja Hussien Arief Hussien; ', Tian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the profile of Technological Pedagogical Content Knowledge (TPCK) Biology Teacher prospective students FKIP Riau University. This type of research is a descriptive study conducted in FKIP Biology Education Studies Program, University of Riau in September-November 2014. The sample was a student of Biology Education FKIP Riau University class of 2011 and 2012. The sampling technique is done with purposive. The research instrument in the form of closed and open questionnaire. Closed questionnaire consists of 32 items to measure 7 (seven) TPCK domain, namely: 1. Technological Knowledge, 2. Pedagogical Knowledge, 3. Content Knowledge, 4. Technological Pedagogical Knowledge, 5. Technological Content Knowledge, 6. Pedagogical Content Knowledge, 7. Technological Pedagogical Content Knowledge. The results show the ability of student teachers in applying TPCK biology are at good criteria with a mean of 3.41. Thus, student teachers FKIP Biology, University of Riau have been able to organize learning biology-based information and communication technology (ICT). While the correlation between TPCK against prospective student GPA Biology Teacher shows the items that exert significant influence Technological Knowledge ie with a percentage of 13.1%.Keywords: Technology, Pedagogy, Content, Technology Pedagogical Content Knowledge, Biology Teacher Prospective Students.